2018
DOI: 10.4103/ijccm.ijccm_164_18
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mechanical insufflation–Exsufflation and endotracheal suctioning in mechanically ventilated patients: Effects on respiratory mechanics, hemodynamics, and volume of secretions

Abstract: Context:Cough assist (CA) is a device to improve bronchial hygiene of patients with secretion in the airways and ineffective cough.Aims:To compare the physiological effects and the volume of secretion of mechanical insufflation–exsufflation (CA device) with isolated endotracheal suctioning in mechanically ventilated patients.Settings and Design:Randomized crossover trial.Materials and Methods:The patients were randomly allocated to the first technique, then the following technique was performed in the next day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 22 publications
0
31
2
Order By: Relevance
“…In this randomized cross-over trial, when inspiratory/expiratory pressures of 50 cmH 2 O were applied, lung compliance improved immediately after the intervention, and 10 minutes thereafter. Despite these encouraging previous results, other publications have consistently failed to nd bene ts (15,16,18). In our study, compliance of the respiratory system increased immediately after CPT + MI-E intervention.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…In this randomized cross-over trial, when inspiratory/expiratory pressures of 50 cmH 2 O were applied, lung compliance improved immediately after the intervention, and 10 minutes thereafter. Despite these encouraging previous results, other publications have consistently failed to nd bene ts (15,16,18). In our study, compliance of the respiratory system increased immediately after CPT + MI-E intervention.…”
Section: Discussioncontrasting
confidence: 79%
“…Nunes et al observed an improvement in SpO 2 after either endotracheal suctioning or MI-E (18), while other publications failed to corroborate these results (15,16). Sanchez-Garcia et al demonstrated an improvement in PaO 2 following MI-E (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…65,66 Only a few studies have investigated the effects of MI-E in critically ill mechanically ventilated subjects. [67][68][69][70][71] The first study was published in 2010 by Bach et al, 67 who reported successful extubation to continuous noninvasive ventilation and MI-E of 155 of 157 subjects with neuromuscular disease considered unweanable after multiple unsuccessful spontaneous breathing trials or extubations. In this first study, the subjects were submitted to MI-E every 20 min while intubated to maintain S pO 2 $ 95% in ambient air.…”
Section: Mechanical Insufflation-exsufflationmentioning
confidence: 99%
“…Interestingly, although the study was underpowered for detection of subgroup effects, patients with COPD as comorbidity (i.e., 14 patients in each group) resulted in significantly less aspirated secretions. Finally, Coutinho et al75 performed a randomized crossover trial in 43 adult patients invasively ventilated for >48 hours to compare the volume of sputum retrieved during MI-E or conventional tracheal suctioning. No significant differences either in the primary outcome or secondary outcomes such as pulmonary mechanics were found between groups.…”
mentioning
confidence: 99%